Improving Student's Englisg Speaking Competence Through Think-Pair-Share Strategy(A Classroom Action Research on the Seventh Grade Students of SMP Negeri 1 Jaten Karanganyar Academic Year 2010/2011) - FATIMAH, FATIMAH (2011)
The problem of seventh grade students in SMPN 1 Jaten was lack of speaking competence. It was caused by the lack of English speaking practice and less motivation of speaking. The objectives of the research were: 1) to find out whether the use of Think-Pair-Share in teaching English improve the students' English speaking competence at the seventh grade in SMPN 1 Jaten, 2) to find out the effectiveness of using Think-Pair-Share in teaching English speaking, and 3) to find out the problems that may appear during the application of Think-Pair-Share in speaking class. The data were collected through observation and tests. They were collected through the students' participation in speaking class. The observation was done in the students' ability to do the exercises, join the group discussion and presentation. The data were supported by the informal interview after speaking class had finished. The findings show that: 1) the use of TPS in speaking class can improve the students' English speaking competence at the seventh grade in SMPN 1 Jaten. 2) The use of TPS is effective in teaching speaking in terms of improving the students' affective factors such as motivation and self confidence, arousing the students' active participation during the speaking class, improving the students' speaking competence, especially the speaking score. 3) The problems appeared during the application of TPS were a few students who still passive in speaking and those who still did not fulfill the Minimum Passing Grade or Kriteria Ketuntasan Minimal (KKM). The research findings implied that TPS can be an alternative strategy to promote the students' speaking competence. Therefore, it is recommended that the English teacher apply it. It is also recommended that the institution socialize the findings since it is useful for English subject. The last is for other researchers to develop the aspect of speaking competence which has not been developed in the research.